PENGEMBANGAN SISTEM GRADER DI JURUSAN ILMU KOMPUTER FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNILA - Mei Rusfandi; Didik Kurniawan; Ardiansyah Ardiansyah (Jurnal Pepadun, 2020)
Grader is a system to complement the demand of online learning system at the Computer Science Department, Faculty of Mathematics and Natural Science, University of Lampung. The existed virtual class system facilitates assessments with automatic correction for assignments and tests. On the other hand, a grader aims to generate automatic correction for programming tasks. This research implements extreme programming method to build a grader system. The system was built using the CodeIgniter PHP framework. Developments carried out in this study include the addition of user categories to admin, editor and participants; as well as the addition of the share code feature. Black box testing was conducted twice to validate the performance of the system, in which fulfilled all the requirements and set to release.